2022
DOI: 10.1007/s00595-022-02497-5
|View full text |Cite
|
Sign up to set email alerts
|

Tele-assessment of bandwidth limitation for remote robotics surgery

Abstract: Purpose We investigated the communication bandwidth (CB) limitation for remote robotics surgery (RRS) using hinotori™ (Medicaroid, Kobe, Japan). Methods The operating rooms of the Hokkaido University Hospital and Kyushu University Hospital were connected using the Science Information NETwork (SINET). The minimum required CB for the RRS was verified by decreasing the CB from 500 to 100 Mbps. Ten surgeons were tested on a task (intracorporeal suturing) at different levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…(Figure 5). Ebihara et al reported that telerobotic surgery can be performed safely with a communication bandwidth of 150 Mbps or higher, and even when the communication bandwidth is insufficient, image degradation can be avoided by considering the image compression ratio 13 . In addition, Edward et al reported that telesurgery can be performed at bit rates of 8–20 Mbps 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Figure 5). Ebihara et al reported that telerobotic surgery can be performed safely with a communication bandwidth of 150 Mbps or higher, and even when the communication bandwidth is insufficient, image degradation can be avoided by considering the image compression ratio 13 . In addition, Edward et al reported that telesurgery can be performed at bit rates of 8–20 Mbps 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Ebihara et al reported that telerobotic surgery can be performed safely with a communication bandwidth of 150 Mbps or higher, and even when the communication bandwidth is insufficient, image degradation can be avoided by considering the image compression ratio. 13 In addition, Edward et al reported that telesurgery can be performed at bit rates of 8-20 Mbps. 14 Therefore, there is a possibility that remote robotic surgery can be performed even when the communication bandwidth is not sufficient, as in the case of mobile communication.…”
Section: Discussionmentioning
confidence: 99%
“…The RTT time was a median of 4 [2][3][4][5][6][7][8][9][10][11][12] msec. The delay between encoder and decoder was 25 msec of the encoder-decoder processing time.…”
Section: Transmission Delay Timementioning
confidence: 99%
“…We conducted a demonstration of telerobotic surgery using a commercial line as a preliminary study in February 2021, and reported that it was possible to build a communication environment conducive to remote surgery 7 . In August 2021, hinotori™️ (Medicaroid Corporation) was successfully operated remotely over a distance of 2000 km using a Science Information NETwork (SINET) 8 . However, since the communication delay and the video transmission information delay vary depending on the communication environment to be constructed and the robot to be used, it is necessary to verify communication environments and the robots involved in various combinations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation